Investigation of the Nucleation Kinetics of Bi and Î”-Bi2O3 During Electro-Deposition on Substrate ITO - Lghazi, Y.; Bimaghra, I.; El Bachiri, A.; Elmerzouki, K.; Youbi, B.; Lasri, H. (International Journal of Engineering and Technology, 2018)
Bismuth and there oxide (Î´-Bi2O3) thin films were deposited on ITO substrates by electro-deposition method. First a cyclic voltammetry study, over a wide range of potentials, with the mounting of three electrodes and an electrolytic solution of 0.01M Bi(NO3)3.5H2O, 0.25M tartaric acid and 2.5M KOH. Towards cathode potential -900mV / SCE we observed the peak of reduction of Bi (III) to Bi (0). When scanning towards increasing potentials we observed a nucleation loop on the electrode, which indicates that there is nucleation, followed by an oxidation peak of Bi (0) to Bi (III). Then we carried out a study of the germination kinetics by carrying out transients current at potentials close to that of reduction peak. The comparison of our transients curves obtained by the chrono-amperometric method with the theoretical transients curves of Charifker and Hills allows us to say that the nucleation is three-dimensional and progressive at a poteniel of -940mV and -950mV but, at a potential of -980 that seems rather for small deposition time a progressive nucleation that can change to an instantaneous nucleation. The characterization of one sample was carried out by X-Ray diffraction, showed that the film was pseudo-fluorite structure. The preferred orientation of the crystallites is (200) for the as deposited film.Â